Cognitive Improvement Following Lead Chelation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1993)
The short (7 weeks) and long (6 months) term effects of lowered blood lead levels on cognitive performance were measured in 154 previously untreated lead-poisoned children, aged 13 to 87 months, examined at the Department of Pediatrics, Albert Einstein College of Medicine, Montefiore Medical Center, Bronx, NY.